PEMBERIAN BIOCHAR TEMPURUNG KELAPA DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL KUBIS BUNGA (Brassica oleraceae var. botrytis L.) PADA TANAH GAMBUT PEDALAMAN (Biochar Coconut Shell and Liquid Organic Fertilizer on Growth and Yield of Cauliflower (Brassica oleraceae var.Botrytis L.) On Peat Soil) - rudin, syah (Universitas Palangka Raya, 2016)
ABSTRACTThe purpose of research was to find the interaction of biochar coconut shell applying and liquidorganic fertilizer Nasa on growth and yield cauliflower on peat soil. Research was using completelyrandomized design (CRD) with two factors. The first factor was the provision of biochar coconut shell(B) which consists of three levels, namely: 0, 4,and 6 t ha-1. The second factor was the concentration ofliquid organic fertilizer Nasa (N) which consists of 4 levels, namely:0, 4, 6, and 8 cc.L-1 water.Variables measured were : plant height, number of leaves, leaf area, flower diameter and weight offlowers.The results showed that there was an interaction between the provision of biochar coconutshell and liquid organic fertilizer on plantheight, number of leaves, leaf area, flower diameter andweight flower. Giving biochar coconut shell at 6 t ha-1 and liquid organic fertilizer Nasa 8 cc.L-1 water,coud promote the growth and yield of cauliflower with the best result of flower weight at 235.18g.plant-1.Key word : Cauliflower, coconut shell biochar, Nasa liquid organic fertilizer and peat soil.